Trains - Graham, Ian, 1953-; Biesty, Stephen (Somerville, Massachusetts : Templar Books, an imprint of Candlewick Press, 2017)
Looks at the inner workings of a selection of railroad trains, including steam trains, electric trains, heavy-duty diesel trains, and high-speed trains, in a board book with lift flaps.
Cover title.
"Lift the flaps to get the inside story on the world's best trains!"--Cover.
Keywords: Railroad trains -- Juvenile literature; Lift-the-flap books -- Specimens; Board books; Railroad trains; Lift-the-flap books; Toy and movable books; Board books; Railroads; Toy and movable books; Board books for children